Acquired lymphangiectasis associated with a surgery scar from a congenital hemangioma. - Tian, Ting; Zhang, Ru-zhi (European Journal of Pediatric Dermatology, 2015)
Acquired lymphangiectasis (AL) occurs due to the blockage of deep lymphatic vessels. The latter is responsible for dilated dermal lymphatic channels that can induce superficial vesicle formation. We report an 11-year-old girl presented to us with a 10-year history of translucent thick-walled vesicles, which was diagnosed as AL according to the typical clinical lesions.